Evaluación de la necesidad del pago de una remuneración a los nuevos proyectos de generación para garantizar su cierre financiero (2019)
It is the governments obligation to develop the necessary mechanisms to guarantee trust and the continues use of the electrical energy, even in the most extreme conditions. In countries like Colombia, with an energy mix primarily hydroelectric, whom constant exposure to natural occurring weather phenomenon such as El Niño, that increase the summer temperatures and decrease the capacity to generate electricity due to reduced water resources, its necessary to stimulate investment in new centrales that generate trust in the system, mainly in these drought periods. The adopted mechanism in Colombia, to ensure the correct and continuous functioning of the system, is a periodic payment to the generators that dispose themselves to offer energy service of necessary and sufficient to guarantee the trust in the system, called Reliability Charge “Cargo por Confiabilidad”, but nevertheless, this trust isn’t free and must be paid by all the users of the system. The mechanism consists of the auction of Firm Energy Obligation (OEF – Obligaciones de Energía en Firme), within the proprietary agents or those who represent commercial plants an/or units of generation to whom have been assigned the firm energy to the Reliability Charge classified in plants and/or new generating units or special plants and/or existing generating units. With this work, the aim is to establish the need to pay to achieve the financial closure of the new generating projects, by financial valuation of the generating projects, one thermic and one hydraulic, during a 20 year time period, from the projected income by sale of energy in the electric energy stock and valuation of Internal Rate of Return of the projects, with or without income, generated by the payment for the Reliability Charge.